Incidence of injuries in rhythmic gymnastics - Oltean, A.; Rusu, M. M.; Copoiu, N.; Calin, M. F. (Science, Movement & Health, 2017)
Aim. The paper aims to analyze the situation of the rhythmic gymnastics injuries in Romania as a consequence of wear produced in the training through the very large number of repetitions of biomechanically difficult elements required by the Score Code. Methods. We applied between October 2016 and April 2017 a questionnaire with 10 questions to legitimate athletes practicing rhythmic gymnastics in the clubs participating in national and international competitions in our country. Results. The 30 athletes of our research aged 12-13 years present approximately equally injured precent ankles and spine (lumbar level). Conclusions. This study can be a support for the specialists in the field to develop training plans that do not lead to injuries of the athletes in order to avoid mistakes in choosing the means and methods of learning, consolidating and improving the elements with high risk of injury.